Altered brain microstructure in association with repetitive subconcussive head impacts and the potential protective effect of jugular vein compression: a longitudinal study of female soccer athletes. Issue 24 (15th October 2018) - Myer, Gregory D; Barber Foss, Kim; Thomas, Staci; Galloway, Ryan; DiCesare, Christopher A; Dudley, Jonathan; Gadd, Brooke; Leach, James; Smith, David; Gubanich, Paul; Meehan III, William P; Altaye, Mekibib; et al.
Abstract : Purpose: To (1) quantify white matter (WM) alterations in female high school athletes during a soccer season and characterise the potential for normalisation during the off-season rest period, (2) determine the association between WM alterations and exposure to repetitive subconcussive head impacts, and (3) evaluate the efficacy of a jugular vein compression collar to prevent WM alterations associated with head impact exposure. Methods: Diffusion tensor imaging (DTI) data were prospectively collected from high school female soccer participants (14–18 years) at up to three time points over 9 months. Head impacts were monitored using accelerometers during all practices and games. Participants were assigned to a collar (n=24) or non-collar group (n=22). The Tract-Based Spatial Statistics approach was used in the analysis of within-group longitudinal change and between-group comparisons. Results: DTI analyses revealed significant pre-season to post-season WM changes in the non-collar group in mean diffusivity (2.83%±2.46%), axial diffusivity (2.58%±2.34%) and radial diffusivity (3.52%±2.60%), but there was no significant change in the collar group despite similar head impact exposure. Significant correlation was found between head impact exposure and pre-season to post-season DTI changes in the non-collar group. WM changes in the non-collar group partially resolved at 3 months off-season follow-up. Discussion: Microstructural changes in WM occurred during a season of female high school soccer among athletes who did not wear the collar device. In comparison, there were no changes in players who wore the collar, suggesting a potential prophylactic effect of the collar device in preventing changes associated with repetitive head impacts. In those without collar use, the microstructural changes showed a reversal towards normal over time in the off-season follow-up period.